Gender differences in adolescents' perceptions toward dentists using the Japanese version of the dental beliefs survey: a cross-sectional survey - Hiroyuki Karibe; Yuichi Kato; Kisaki Shimazu; Ayuko Okamoto; Masahiro Heima (BMC, 2019)
Abstract Background While adult women show greater dental anxiety than adult men, few studies have examined gender differences in adolescent perceptions of dentists. Therefore, this cross-sectional study aimed to evaluate the gender differences in adolescents' perceptions toward dentists by using the Japanese version of the Dental Beliefs Survey (DBS) and the factor structure of the DBS. Methods We conducted surveys at schools, and 957 Japanese adolescents (403 girls and 554 boys, aged between 13 and 15 years) participated in this study. To assess their confidence in dentists, participants were asked to complete the self-reported, 15-item Japanese version of the DBS. We performed a Welch's t-test and a one-way analysis of variance to assess differences in DBS scores by gender and age. Factor analysis (principal components, varimax rotation) was used to assess the scale's factor structure. Results A significant gender difference was observed in the DBS scores (P = 0.018), suggesting that boys exhibit greater negative perceptions toward the behavior of dentists than girls. However, there was no significant difference found among ages. The factor analysis yielded two results: Factor 1, "trust" (seven items); and Factor 2, "lack of control" (five items). Notably, the factor structure differed according to gender. As such, by including only factors with eigenvalues above 1.0, the DBS for girls comprised "trust" (seven items) and "communication" (three items), while that for boys comprised "lack of control" (six items) and "belittlement" (six items). Conclusions This study identified two factors of differing strengths pertaining to the confidence of Japanese adolescents in dentists. Gender differences in perceptions toward dentists were observed. Accounting for these differences may improve the effectiveness of strategies to lower dental anxiety and foster positive dental beliefs in young patients.